Highway Engineering - Yaghoubi, Hamid (IntechOpen, 2017)
Highway engineering is an engineering discipline branching from civil engineering that involves the planning, design, construction, operation, and maintenance of roads, bridges, and tunnels to ensure safe and effective transportation of people and goods. The book Highway Engineering includes the main topics and the basic principles of highway engineering and provides the full scope of current information necessary for effective and cost-conscious contemporary highway. The book reflects new engineering and building developments, the most current design methods, as well as the latest industry standards and policies. This book provides a comprehensive overview of significant characteristics for highway engineering. It highlights recent advancements, requirements, and improvements and details the latest techniques in the global market. Highway Engineering contains a collection of the latest research developments on highway engineering. This book comprehensively covers the basic theory and practice in sufficient depth to provide a solid grounding to highway engineers. This book helps readers maximize effectiveness in all facets of highway engineering. This professional book as a credible source and a valuable reference can be very applicable and useful for all professors, researchers, engineers, practicing professionals, trainee practitioners, students, and others interested in highway projects.